Contabilidade de gestão no terceiro setor: estudo empírico em instituições particulares de solidariedade social - Santos, M. (2014)
In today’s economy, state and philanthropic support is extremely selective, failing to address all requests of social sector institutions. Private non-profit charity institutions (IPSS) – social institutions par excellence – are also affected by the reality of this constraint and, as such, are expected to apply the allocated resources effectively and efficiently in order to justify receiving awards. In order to understand to what extent the management of these organisations have information to support their decision-making, this research sought to relate the level of maturity of the management accounting systems with elements influencing organisational capacity: stakeholders and human and financial resources. Through a survey of 61 IPSS, it was found that, even when it was possible to obtain management information to identify deficit situations, the accounting systems in use do not guarantee support for decision-making. As justification, institutions indicate possessing sufficient information, which can reveal a non-perception of obsolete systems, highlighting the need for training in third sector organisations. Atualmente, o apoio estatal e filantrópico é extremamente seletivo, não conseguindo responder a todas as solicitações das instituições sociais. As Instituições Particulares de Segurança Social são também afetadas por esta restrição e, nesse sentido, espera-se que apliquem os recursos atribuídos de forma eficaz e eficiente de modo a justificar essa atribuição. Visando estudar em que medida estas organizações têm informação para a tomada de decisão, esta investigação relaciona o grau de desenvolvimento dos sistemas de contabilidade de gestão com os elementos influenciadores da capacidade organizacional, recursos humanos e financeiros, e com os stakeholders. Com base num inquérito a 61 IPSS, constatou-se que, mesmo sendo possível obter informação que identifique situações deficitárias, os sistemas de contabilidade de gestão implementados não garantem o suporte à tomada de decisão. Como justificação, as instituições indicam possuir informação suficiente, o que pode revelar a não perceção de sistemas obsoletos, evidenciando necessidades de formação nesta área.